Effect of Cognitive Stimulation Therapy on Quality of Life: A Critical Review. (2nd July 2020) - Chao, Iris C. I.; Nicpon, Katarzyna; Roduta Roberts, Mary
Abstract: Aims: To determine the strength of the evidence regarding cognitive stimulation therapy (CST) to improve the quality of life of people with mild-to-moderate dementia. Methods: A critical literature review was conducted to evaluate the methodological quality of relevant studies. The Guidelines for Critical Review (GCR), the Jadad scale, and the Effective Public Health Practice Project (EPHPP) quality assessment tool were used to complete a critical appraisal of the selected articles. Results: Eight publications were retrieved for review. Three studies indicated significant improvements in overall quality of life. The global EPHPP scores showed two studies were of strong methodological quality, while four were moderate, and two were weak. Conclusions: Results indicate the potential usefulness of CST for improving quality of life for older adults with mild-to-moderate dementia. With expertise in psychosocial interventions and dedication to evidence-based practice, occupational therapists (OTs) are well-positioned to implement CST.